The roots of Agnosticism in the 19th Century’s English Thought - Velarde Lombraña, Julián (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Agnosticism developed by Huxley has its epistemological roots in Kant’s critical philosophy. Kant and Huxley’s theories of knowledge share a common foundation: the factum and development of science. Here, we research into: a) Agnostics’ connexion to Kantian criticism; b) the relationship between agnosticism and science, and c) the relationship between agnosticism and religion.